2017
DOI: 10.1501/vetfak_0000002777
|View full text |Cite
|
Sign up to set email alerts
|

Balık ve yetiştirme suyu kökenli Aeromonas izolatlarının antimikrobiyal duyarlılıklarının saptanması

Abstract: Özet:Aeromonas türleri sucul ortamda yaygın olarak bulunan ve hem soğuk kanlı hayvanlarda hem de insanlar da çeşitli hastalıklara neden olabilen Gram negatif basillerdir. Bu çalışma, ülkemizde balık ve yetiştirme sularından izole edilmiş olan Aeromonas izolatlarının antimikrobiyal duyarlılık profillerinin belirlenmesi amacıyla gerçekleştirildi. Çalışmaya üç farklı coğrafik bölgeden (Karadeniz, Akdeniz, Ege) izole edilmiş olan toplam 45 Aeromonas izolatı (20 A. sobria, 10 A. hydrophila, dokuz A. salmonicida, dö… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…However, previous studies have revealed the necessity of microbiological examination of the inlet waters of fish farms. In this sense, it has been reported that A. salmonicida, A. hydrophila and A. sobria species are isolated from the inlet water from different fish farms belonging to the Black Sea Region of Turkey (Onuk et al 2017). Similarly, in the present study, different species belonging to the genus Aeromans were found in the inlet water in 6 of 11 farms.…”
Section: Discussionsupporting
confidence: 76%
“…However, previous studies have revealed the necessity of microbiological examination of the inlet waters of fish farms. In this sense, it has been reported that A. salmonicida, A. hydrophila and A. sobria species are isolated from the inlet water from different fish farms belonging to the Black Sea Region of Turkey (Onuk et al 2017). Similarly, in the present study, different species belonging to the genus Aeromans were found in the inlet water in 6 of 11 farms.…”
Section: Discussionsupporting
confidence: 76%